2018
DOI: 10.1021/acsami.7b18324
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructured Nanorings of Fe−Fe3O4@C Hybrid with Enhanced Microwave Absorption Performance

Abstract: Microwave absorption is a critical challenge with progression in electronics, where fine structural designing of absorbent materials plays an effective role in optimizing their microwave absorption properties. Here, we have developed FeO@C (FC) and Fe-FeO@C (FFC) hybrid nanorings via a hydrothermal method coupled with a chemical catalytic vapor deposition technique. FC and FFC hybrid nanorings have fine carbon coating while their size can easily be tunable in a certain range from 80-130 to 90-140 nm. The optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(85 citation statements)
references
References 44 publications
4
81
0
Order By: Relevance
“…6. Sample #4 presents the highest attenuation constant in the Ku-band (12)(13)(14)(15)(16)(17)(18), which is consistent with its excellent microwave absorption in the Ku-band (as seen in Fig. 7d).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…6. Sample #4 presents the highest attenuation constant in the Ku-band (12)(13)(14)(15)(16)(17)(18), which is consistent with its excellent microwave absorption in the Ku-band (as seen in Fig. 7d).…”
Section: Resultssupporting
confidence: 72%
“…Sample #3 presents poor reection loss in the 2-18 GHz range, which can be attributed to the poor impedance matching because its permittivity is much larger than its permeability. However, Sample #4 presents excellent microwave absorption properties in the Ku-band (12)(13)(14)(15)(16)(17)(18) at the coating thickness of 1 mm; the maximum RL value reaches À33 dB at 17.6 GHz and the bandwidth covers the 15.04-18.00 GHz range. As the coating thickness increases to 1.5 mm, the RL peak shis to the position at 11.12 GHz with the maximum RL value of À26.3 dB and the bandwidth covers the 9.8-12.88 GHz range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LSPRs supported by copper nanoporous structures are revealed by numerical simulations which shows intense electromagnetic field enhancements around nanopores. Compared with other hollow‐core and porous structures enabled by dedicated synthesize or growth methods, our work provides an efficient strategy to prepare copper nanoporous structures, which is potentially very promising in developing SERS platforms and optofluidic sensing systems for molecular diagnostics in future.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many nanomaterials have been proved to exhibit excellent absorbing properties, such as Fe 3 O 4 (Jia et al, 2010), SiC (Kuang et al, 2019), RGO aerogels (Zhang M. et al, 2019), C@CoFeO@MnO 2 (Feng et al, 2020), Fe 3 O 4 @NPC (Xiang et al, 2019), and PbS (Pan et al, 2017). In addition, many studies have shown that most of the nanocomposites have synergistic effects, which will be very beneficial to the absorbing properties of the materials (Liu et al, 2017;Jian et al, 2018;Ma et al, 2018). The typical composites are composed of matrix and filler.…”
Section: Introductionmentioning
confidence: 99%